An Error Analysis: Problem Solving of The Maximum and Minimum Derivative Values With Newman’s Error Analysis - Terri Murizki Anugrah; Tri Atmojo Kusmayadi (Journal of Mathematics and Mathematics Education, 2019)
This study aimed to describe the errors made by students in solving of maximum and minimum derivative values problem-solving test. The research method used is the descriptive qualitative method. The subjects consisted of five twelfth grade students of senior high school in Puding Besar who were selected by purposive sampling. The instrument used in this study are derivative problem-solving test and interviews. The results of student answers were analyzed using the Newman’s error analysis. Based on the results of the analysis, the most common error made by students were errors in the comprehension errors. The most students do not understand the concept of solving the problems of maximum and minimum derivative values. Students only work on algebraic questions without using concepts of maximum and minimum derivative values